A QUALITATIVE STUDY ON ENHANCING EMOTIONAL REGULATION AND SOCIAL ADJUSTMENT IN CHILDREN WITH AUTISM SPECTRUM DISORDER: THE IMPACT OF INTEGRATED MULTIDISCIPLINARY TREATMENT (Journal of Medical & Health Sciences Review, 2026)
This qualitative study explored the experiences and perceptions of parents regarding the impact of integrated multidisciplinary treatment on emotional regulation and social adjustment in children with Autism Spectrum Disorder (ASD). Using a phenomenological research design, semi-structured interviews and narrative accounts were collected from five parents whose children had participated in combined behavioral, occupational, and speech-language interventions. Data were analyzed using thematic analysis following Braun and Clarke’s framework. The findings revealed five overarching themes: improvement in emotional regulation, development of social skills, importance of structured routines, active parental involvement, and challenges associated with treatment implementation. Parents reported noticeable reductions in emotional outbursts, enhanced communication abilities, increased peer interaction, and greater adaptability to daily routines. Despite financial, emotional, and logistical challenges, parental engagement emerged as a critical factor in sustaining therapeutic gains. The study highlights the value of holistic, family-centered, and multidisciplinary approaches in improving emotional and social outcomes for children with ASD and underscores the need for accessible integrated services in developing contexts.